The migration through Europe and wintering in West Africa of Curlew Sandpipers - Wilson, J R; Czajkowski, M A; Pienkowski, M W (Wildfowl, 1980)
The migration of Curlew Sandpipers Calidris ferruginea in Europe and north-west Africa is reviewed by bringing together sightings of visible migration, counts at resting sites, and ringing recoveries to put into perspective the occasional influxes of this species into north-west Europe. Data on counts, catching, weights and moult obtained in north-west Africa are presented and the species’ wintering status in west Africa is reviewed. Most Curlew Sandpipers occurring in these regions appear to migrate between northern USSR and West Africa via European Russia and the Black and Mediterranean seas. There is a smaller regular autumn passage through N W. Europe but these birds tend to join the majority in the more easterly route in spring. In years of high breeding success and certain weather patterns over northern Europe large numbers of juveniles are displaced westwards resulting in the occasional large influxes into Western Europe. Unlike the regular N.W. European component, these birds use a more easterly course in later autumns. The early departure of males from the breeding grounds results in different migration and moult schedules between the sexes but it is not known if wintering grounds are also different. More work is required in west and central Africa to clarify the winter distribution of this species.